2007
DOI: 10.1097/01.ijg.0000212290.08540.93
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Cerebral Blood Flow and Central Visual Function in Primary Open-angle Glaucoma

Abstract: Our findings suggest that in certain primary open-angle glaucoma patients diminished central visual function may be one manifestation of widespread cerebrovascular insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Cerebrovascular insufficiency in glaucoma has been reported by a few previous clinical studies, and includes abnormal CBF patterns, diffuse WM lesions, lacunar infarcts, and hemodynamic disturbances in the middle cerebral artery (MCA). [36][37][38][39][40][41][42][43] We have previously reported insufficiency in the hemodynamics and vasoreactivity of the PCA, the main supplying vessel of the posterior visual pathways, in POAG. 19 A recent study reported reduction in the resting CBF in the primary visual cortex and its correlation with the loss of visual function in patients with POAG.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebrovascular insufficiency in glaucoma has been reported by a few previous clinical studies, and includes abnormal CBF patterns, diffuse WM lesions, lacunar infarcts, and hemodynamic disturbances in the middle cerebral artery (MCA). [36][37][38][39][40][41][42][43] We have previously reported insufficiency in the hemodynamics and vasoreactivity of the PCA, the main supplying vessel of the posterior visual pathways, in POAG. 19 A recent study reported reduction in the resting CBF in the primary visual cortex and its correlation with the loss of visual function in patients with POAG.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Furthermore, an ultrasound study of cerebral hemodynamics found diminished central visual function to be one manifestation of widespread cerebrovascular insufficiency in glaucoma. 24 The vascular dysfunction in the retrobulbar blood vessels measured by CDI may also appear as an observable vasospasm in select glaucoma patients. 22 Vasospasm within the blood vessels supplying the optic nerve head and retinal ganglion cells may lead to accelerated loss of visual function and increased rates of glaucomatous disease progression.…”
Section: Color Doppler Ultrasound Imagingmentioning
confidence: 99%
“…63 There is a significant correlation between the mean flow velocity of middle cerebral arteries (MCAs) and the mean defect of the central visual field, logMAR visual acuity, and contrast sensitivity in glaucoma patients, suggesting that, in certain POAG patients, diminished central visual function may be one manifestation of widespread cerebrovascular insufficiency. 64 In the primary visual cortex, ocular dominance columns driven by the ipsilateral and contralateral eyes may be supplied by a different microvascular system. 65,66 The vascular insufficiency in regions receiving retinal input from the glaucomatous eye is likely to be more severe than that related to the fellow eye, which may affect the task-related blood flow increase during visual stimuli to the glaucomatous eye and lead to a reduced BOLD response.…”
Section: Task-related Bold Response Decrease In the Primary Visual Comentioning
confidence: 99%